Dampak Aplikasi Kencan Online Tinder Terhadap Kasus Pelecehan Seksual Dikalangan Remaja - Yuni Sarah; Usamah Usamah; Irmawati Irmawati; Muhammad Syukur; Ibrahim Arifin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Online or online dating applications are currently very trending and are currently in great demand by many people in finding a mate and making new friends. The use of online dating applications is considered more effective in helping someone get a friend or partner compared to the traditional methods that were previously used. This is of course inseparable from the development of information and communication technology that has changed the way individuals interact with other individuals. It is unavoidable that many online dating applications have sprung up to find a mate like Tinder which only uses the medium of a finger to melt someone's heart. However, many online dating applications today use it for things that are dangerous and can harm some people, such as fraud and sexual violence. This article focuses on the discussion regarding the impact of online dating application users on irresponsible crime rates, such as sexual harassment among adolescents. This study aims to analyze the impact of using online dating applications on sexual violence among adolescents. After that the authors conducted interviews and distributed questionnaires to informants about their experiences using the Tinder application.